Feed Passage Rate in Broiler Chickens Fed on Rye-Based Diet Supplemented with Essential Oil Components - Lee , Kyung-Woo (International Journal of Poultry Science, 2014)
The present study was conducted to monitor feed passage rate in broiler chickens fed on either corn-or rye-based diet, or the rye-based diet supplemented with essential oil components. A total of 80 one-day old female broiler chickens were randomly allotted into 5 dietary treatments. There were five experimental diets; corn-based diet, rye-based diet, rye+100 ppm thymol, rye+100 ppm cinnamaldehyde and rye+100 ppm CRINA® Poultry. At day 7, rye-based diet-fed chickens exhibited stunted growth and increased vent score compared with the corn-based diet-fed counterparts. When essential oil components added into the rye-based diet, no clear reduction in stunted growth and vent score was observed in all treated groups. The feed passage rate was monitored at 28-days of age. It was found that time required for 50% of marker excretion was not significantly different between experimental groups including the two control groups i.e., corn versus rye groups. Similarly, excretion curve pattern was almost identical between experimental groups. In summary, broiler chickens fed on rye-versus corn-diet showed identical feed passage rate at 4 weeks of age without affecting body weight and feed intake. In addition, supplementation of essential oil components into the rye-based diet did not affect feed passage rate.